Diversity of Micromonospora in Malaysian Mangrove Rhizosphere Soil - A, Smet; S, Parameswari; S, Vikineswary (Malaysian Journal of Science, 2002)
Seventy putative micromonosporae were assigned to 12 single and multi- membered colour groups based on their colony colour produced on modified micromonospora (MMS) agar medium. The strains produced well-developed substrate mycelium of approximately 0.2 Ã¢â‚¬â€ 0.4 jtm in diameter and had $meso$-DAP in the cell wall hydrolysates. Single spores having an average diameter of 0.4 to 1.0 $μ m$ were produced on substrate mycelium. A range of diffusible pigments produced by 29% of the isolates on thc MMS agar plates included: brown, 13%; yellow, 10% and purple, blue, and black at 1% each. The results of the cell wall analysis, cultural and morphological characteristics of the selected strains tentatively indicated that they belonged to the genus Micromonospora Orskov 1923.